In Vivo Evaluation of a Closed Loop Monitoring Strategy for Induced Paralysis - Ramakrishna, Deepak; Behbehani, Khosrow; Klein, Kevin; Mokhtar, Jeffrey; von Maltzahn, Wolf W.; Eberhart, Robert C.; Dollar, Michael (Journal of clinical monitoring and computing, 1998)
Reliable closed loop infusion systems for regulating paralysis level can be a great convenience to the anesthesiologists in automating their task. This paper describes the in vivo performance evaluation of a self-tuning controller that is designed to accommodate large variations in patient drug sensitivity, drug action delays and environmental interfering noise. The infusion system was evaluated in six adult mongrel dogs. Following the manual induction of paralysis by an anesthesiologist, the controller regulated the infusion of vecuronium to maintain a desired level of paralysis. The integrated EMG response of the hypothenar muscle to a train-of-four stimulation of the ulnar nerve quantified the depth of paralysis. The controller's robustness was tested by contaminating the sensed twitch signal with electrocautery noise and electrode disconnection. The controller reached the initial level of paralysis of 100% in about 4.0 minutes and arrived at the desired level of 90% with an overshoot of 6.38% (+/-6.82). It maintained the desired level of paralysis with a 2.04% (+/-1.20) mean offset at 90% and 0.4% (+/-0.5) mean offset at 80% steady state level, respectively. The mean infusion rate to sustain 90% and 80% paralysis were 2.70 (+/-2.05) and 2.15 (+/-2.57) ((mg/kg)/min), respectively. The system adapted to a large variation in the sample subject drug sensitivity. It remained stable despite large amplitude disturbances and maintained the paralysis at the desired level following the removal of the disturbances.